Does Suburbanization Cause Obesity? - Maryam Naghsh Nejad; Amanda Ross (European Regional Science Association (ERSA), 2014)
In this paper, we examine the effect of suburbanization on obesity rates. Our study is an improvement over the existing literature because we will use county level data for our analysis, enabling us to look at the effect of moving from the central city to the suburbs. Previous research has only had health data at the MSA level, and therefore could not look at the effect of highways on obesity rates within an MSA, particularly the suburbs versus the central city. To estimate the relationship between obesity and highways, we will use county-level data on obesity rates from the Behavioral Risk Factor Surveillance System (BRFSS). We merge the obesity information with data on the proposed highway program of 1950 used previously by Baum-Snow (2007). Our results suggest that additional miles of a highway system increase obesity rates in urban areas.
Keywords: R23; R20; 330; suburbanization; obesity